The role of a mindful movement-based program (Movimento Biologico) in health promotion: results of a pre-post intervention study - Spaccapanico Proietti, Stefano; Chiavarini, Manuela; Iorio, Francesco; Buratta, Livia; Pocetta, Giancarlo; Carestia, Roberta; Gobbetti, Camilla; Lupi, Chiara; Cosenza, Antonio; Sorci, Guglielmo; Mazzeschi, Claudia; Biscarini, Andrea; et al. (Frontiers in Public Health, 2024)
Introduction Mindful movement is a comprehensive approach that integrates various bodily, emotional and cognitive aspects into physical activity, promoting overall well-being. This study assessed the impact of a mindful movement program, known as Movimento Biologico (MB), on participants psychological well-being (PWB), positive mental health (PMH), sense of coherence (SOC), and interoceptive awareness. Methods MB program was conducted for students attending the bachelor’s degree in Kinesiology and Sport Sciences of University of Perugia over 8 weeks (from October 16 to November 27, 2022). Participants were requested to fill in four questionnaires before and after the MB program: (1) 18-item PWB scale; (2) 9-item PMH scale; (3) 13-item SOC scale; (4) 32-item scale for Multidimensional Assessment of Interoceptive Awareness (MAIA). Wilcoxon signed-rank tests were used to assess changes, with significance set at p < 0.05. Results Thirty-eight students (mean age 21.2, 60.5% male) participated. Several MAIA subscales, including noticing (p = 0.003), attention management (p = 0.002), emotional awareness (p = 0.007), self-regulation (p < 0.001), body listening (p = 0.001), and trusting (p = 0.001), showed significant improvements. PMH increased significantly (p = 0.015), and there was a significant enhancement in the autonomy subscale of PWB (p = 0.036). SOC and overall PWB also improved, though not significantly. Conclusion The MB program significantly improved participants’ positive mental health and interoceptive awareness. This likely resulted from better recognition and management of positive physiological sensations, a stronger link between physical sensations and emotions, enhanced confidence in one’s body, and increased autonomy.